2020
DOI: 10.1021/acs.jced.0c00313
|View full text |Cite
|
Sign up to set email alerts
|

Solid Liquid Phase Equilibria in the Ternary Systems NaCl–ZnCl2–H2O and MgCl2–ZnCl2–H2O at 298 K

Abstract: The solid−liquid equilibria relationship in the two ternary systems sodium chloride−zinc chloride−water and magnesium chloride−zinc chloride−water at 298 K were investigated based on the isothermal dissolution equilibrium method, integrated with the methods of humid residue, X-ray powder crystal diffraction, and density bottle. According to the determined solubility data combined with the humid residue composition and equilibrium solid phase, the phase diagrams of the two systems were depicted. It is concluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
1
0
1
Order By: Relevance
“…Obviously, the hydrated double salt turned into anhydrous double salt with the increase in temperature. Comparing our study with data from Zhang et al 18 in 298 K, it was observed that the solubility of the solid phase compositions and double salts were compatible with each other.…”
Section: Comparison Of H2o-zncl2-nacl Systems Between 273 and 373 Ksupporting
confidence: 86%
See 2 more Smart Citations
“…Obviously, the hydrated double salt turned into anhydrous double salt with the increase in temperature. Comparing our study with data from Zhang et al 18 in 298 K, it was observed that the solubility of the solid phase compositions and double salts were compatible with each other.…”
Section: Comparison Of H2o-zncl2-nacl Systems Between 273 and 373 Ksupporting
confidence: 86%
“…It was stated that the solubility of ZnCl 2 decreases from 66.6 to 60.37 % and the solubility of NaCl decreases sharply from 26.25 to 5.24 % to the invariant point as shown in the ternary system of NaCl-ZnCl 2 -H 2 O at 273 K, which was conducted by Adiguzel et al 12 Zhang et al implied that the solubility of ZnCl 2 decreases from 80.77% to 77.25% to the invariant point and the solubility of NaCl decreases from 26.71 to 6.24 %. These results show a sharper drop compared to that of ZnCl 2 in the ternary system at 298 K. 18 O n L i n e F i r s t средине. Растворљивост систему натријум-хлорид + цинк-хлорид + вода (NaCl + ZnCl2 + H2O) је испитивана у изотермским условима на температурама 298, 313 и 333 K. Schreinemakers-ова графичка метода је коришћена за анализу течне и чврсте фазе и за одређивање састава испитиваног система.…”
Section: Discussionunclassified
See 1 more Smart Citation